Analisis Kontribusi Retribusi Penerimaan Pelayanan Pasar Terhadap Retribusi Daerah Kota Banjarmasin - Maimunah; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to determine the contribution, effectiveness, and potential of Market service retribution acceptance on regional retribution in Banjarmasin. The data was used in secondary and primary data with research samples selected by purposive random sampling as many as six markets from 64 markets in Banjarmasin. This data analysis technique using descriptive analysis with the quantitative method. This resulting study indicates that the contribution of receipt of market service retribution acceptance on regional retribution in Banjarmasin during the 2011-2017 budget year was still inferior. However, the market service retribution condition in 2016 had a contribution value of 11,510%, classified as not useful because the percentage value was above 10%. Effectiveness of receiving market service retribution in Banjarmasin tends to fluctuate; it happened in 20112017. The potential of receipt of market service retribution on regional retribution in Banjarmasin is 34,82%. The amount of receipt of market service retribution based on regional regulation number 1 in 2016 is 246,89%.